Old Meany Hall, University of Washington, n.d.
Meany Hall was built in 1908 to serve as the auditorium for the Alaska-Yukon-Pacific Exposition. It was demolished in 1965 after suffering extensive damage in an earthquake. Handwritten on image: Meany Hall. Filed in: UW - Meany Hall (Old) (#463).